Low-energy spin dynamics of orthoferrites AFeO3 (A = Y, La, Bi). (14th May 2018) - Park, Kisoo; Sim, Hasung; Leiner, Jonathan C; Yoshida, Yoshiyuki; Jeong, Jaehong; Yano, Shin-ichiro; Gardner, Jason; Bourges, Philippe; Klicpera, Milan; Sechovský, Vladimír; Boehm, Martin; Park, Je-Geun
Abstract: YFeO3 and LaFeO3 are members of the rare-earth orthoferrites family with Pbnm space group. Using inelastic neutron scattering, the low-energy spin excitations have been measured around the magnetic Brillouin zone center. Splitting of magnon branches and finite magnon gaps (̃2 meV) are observed for both compounds, where the Dzyaloshinsky–Moriya interactions account for most of this gap with some additional contribution from single-ion anisotropy. We also make comparisons with multiferroic BiFeO3 ( R3c space group), in which similar behavior was observed. By taking into account all relevant local Dzyaloshinsky–Moriya interactions, our analysis allows for the precise determination of all experimentally observed parameters in the spin-Hamiltonian. We find that different properties of the Pbnm and R3c space group lead to the stabilization of a spin cycloid structure in the latter case but not in the former, which explains the difference in the levels of complexity of magnon band structures for the respective compounds.